Ocena współczesnej kultury Zachodu w nauczaniu Benedykta XVI (Josepha Ratzingera) - Ewa Kozerska (Ksiegarnia Akademicka Publishing, 2021)
The Assessment of the Contemporary Western Culture in the Teaching of Benedict XVI (Joseph Ratzinger)